Complicated mycotic saccular aneurysm of the infra-renal abdominal aorta with infected retroperitoneal hematoma: a clinical case report - Chinaliyev, A. M.; Jussubaliyev, Y. I.; Khassenov, D. T.; Sabyruly, D.; Shaimerden, E. M.; Kapyshev, M. S.; Aleushinov, R. I.; Aitkul, S. Sh.; Yessenbayeva, G. A.; Sagandykov, I. N.; Sultanaliyev, T. A. (Frontiers in Cardiovascular Medicine, 2024)
BackgroundRupture of an abdominal aortic aneurysm (AAA) is a life-threatening emergency, with untreated cases nearing a 100% mortality rate. This case presents a rare complication of AAA rupture with an infected retroperitoneal hematoma, emphasizing the importance of timely diagnosis and a multidisciplinary approach.Case presentationA 59-year-old male presented with lower back pain, fever, and difficulty moving, persisting for three weeks. Imaging revealed a saccular infra-renal AAA rupture with an infected retroperitoneal hematoma. Emergency surgery included extracorporeal subclavian-femoral bypass and aneurysm resection. Despite intraoperative complications, the patient recovered after 16 days in intensive care and was discharged in satisfactory condition. Follow-up CT one month later showed functioning bypasses and clinical improvement.ConclusionThis case illustrates the critical need for early diagnosis and coordinated surgical intervention in complex AAA ruptures complicated by infection. Timely multidisciplinary treatment is crucial to prevent further complications and improve patient outcomes.